2022
DOI: 10.26803/ijlter.21.11.9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding EFL International Students’ Academic Listening Strategies: A Literature Review

Abstract: Academic listening and interaction in international educational settings are essential for academic success. International students’ language proficiency and prior practice in their home countries either facilitate or impede their academic success. Thus, internationalization has become a desirable trend among learners to further their studies in overseas institutions where English is the medium of instruction. Overseas education allows international students to gain new knowledge and improve their academic ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Proficiency in the English language is particularly critical for international students as it directly influences their academic achievements (Martirosyan et al, 2019). Studies have shown that international students often struggle with academic listening strategies, highlighting the importance of tailored language support programs to enhance their comprehension skills (Halali et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Proficiency in the English language is particularly critical for international students as it directly influences their academic achievements (Martirosyan et al, 2019). Studies have shown that international students often struggle with academic listening strategies, highlighting the importance of tailored language support programs to enhance their comprehension skills (Halali et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%